METHOD AND COMPOSITION FOR LIGHTNING PROTECTION - Amsberry, Kevin (2021)
A particulate composition suitable for protection against lightning is disclosed. The particulate composition comprises of a particulate matter comprising a mineral compound, preferably black tourmaline, capable of emitting negatively charged ions continuously, a grinding auxiliary agent, and a liquid medium. The particulate composition is embedded in a substrate, coating or mixed into the granules of composite roofing to protect people, objects and structures from lightning by developing a negatively charged cloaking shield to prevent the attraction of negatively charged lightning from striking. The composition infused or applied on a subject continuously emits negative ions sufficiently producing a protective electromagnetic cloaking shield restricting the wicking action of positive ions up from ground surface and thereby restricting the formation of positive streamers that reach upwards towards the stepped leaders of lightning.